Altered neuronal migratory trajectories in human cerebral organoids derived from individuals with neuronal heterotopia - Klaus, Johannes*; Kanton, Sabina*; Kyrousi, Christina*; Ayo-Martin, Ane Cristina; Di Giaimo, Rossella; Riesenberg, Stephan; O’Neill, Adam C; Camp, J Gray; Tocco, Chiara; Santel, Malgorzata; Rusha, Ejona; Drukker, Micha; et al. (*Equal contributing authors. Nature medicine, 2019)
Malformations of the human cortex represent a major cause of disability1. Mouse models with mutations in known causal genes only partially recapitulate the phenotypes and are therefore not unlimitedly suited for understanding the molecular and cellular mechanisms responsible for these conditions2. Here we study periventricular heterotopia (PH) by analyzing cerebral organoids derived from induced pluripotent stem cells (iPSCs) of patients with mutations in the cadherin receptor-ligand pair DCHS1 and FAT4 or from isogenic knockout (KO) lines1,3. Our results show that human cerebral organoids reproduce the cortical heterotopia associated with PH. Mutations in DCHS1 and FAT4 or knockdown of their expression causes changes in the morphology of neural progenitor cells and result in defective neuronal migration dynamics only in a subset of neurons. Single-cell RNA-sequencing (scRNA-seq) data reveal a subpopulation of mutant neurons with dysregulated genes involved in axon guidance, neuronal migration and patterning. We suggest that defective neural progenitor cell (NPC) morphology and an altered navigation system in a subset of neurons underlie this form of PH.